Relação entre vitamina d e a função pulmonar, autonômica, hemodinâmica, força, nível de atividade física, qualidade do sono, ansiedade e depressão em pacientes com doença pulmonar obstrutiva crônica - BARROSO, Rodrigo Antônio França (2019)
Introduction: Some studies have shown that low serum 25-hydroxyvitamin D levels play an important role in cardiovascular disease and sleep quality. In addition, decreased vitamin D levels have been associated with decreased lung function in patients with chronic obstructive pulmonary disease (COPD). However, little is known about the impact of vitamin D deficiency in patients with chronic obstructive pulmonary disease on autonomic dysfunction, muscle strength and sleep quality. Objectives: To evaluate the relationship between serum vitamin D level and pulmonary, autonomic, hemodynamic function. , sleep quality and physical performance in patients with chronic obstructive pulmonary disease. Methods: This is a cross-sectional study of patients with chronic obstructive pulmonary disease treated at the outpatient clinic of the Asthmatic Patient Assistance Program (PAPA) at the University Hospital of the Federal University of Maranhão. The patients were divided into two groups: the vitamin D deficiency or insufficiency (GD-) group and the vitamin D deficiency (GD +) group. Results: Vitamin D levels did not influence anthropometric, spirometric and hemodynamic variables; GD- presented worse autonomic modulation and worse sleep quality compared to GD +. Conclusion: the present scientific evidence suggests that vitamin D level positively acts on cardiac autonomic modulation and sleep quality, both major factors for quality of life of patients with Chronic Obstructive Pulmonary Disease.